2022
DOI: 10.1038/s41598-022-21446-3
|View full text |Cite
|
Sign up to set email alerts
|

Zn (II)-porphyrin-based photochemically green synthesis of novel ZnTPP/Cu nanocomposites with antibacterial activities and cytotoxic features against breast cancer cells

Abstract: This study focuses on synthesizing novel nanocomposites, zinc(II)tetrakis(4-phenyl)porphyrin/Cu nanoparticles (ZnTPP/Cu-NPs),with antibacterial activity, fabricated through a single-step green procedure. In this regard, the self-assembly of ZnTPP was carried out through an acid–base neutralization method to prepare ZnTPP nanoparticles. Then, the copper nanoparticles (Cu-NPs) were grown on ZnTPP nanoparticles through a visible-light irradiated photochemical procedure in the absence and presence of polyacrylic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The nonappearance of these two signals in the spectra of ZnTPP indicates the zinc coordination in the complex. Moreover, regarding the spectrum of H 2 TPP, the signal at 1606 cm −1 , which is attributed to the C=N stretching vibration of pyrrole, splits into two peaks at around 1595 and 1652 cm −1 indicating the presence of the Zn–N coordination band in the spectra of the prepared ZnTPP NPs which have shifted to 1630 and 1750 nanocomposites formation 24 , 40 42 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The nonappearance of these two signals in the spectra of ZnTPP indicates the zinc coordination in the complex. Moreover, regarding the spectrum of H 2 TPP, the signal at 1606 cm −1 , which is attributed to the C=N stretching vibration of pyrrole, splits into two peaks at around 1595 and 1652 cm −1 indicating the presence of the Zn–N coordination band in the spectra of the prepared ZnTPP NPs which have shifted to 1630 and 1750 nanocomposites formation 24 , 40 42 .…”
Section: Resultsmentioning
confidence: 97%
“…2 Ad).
Figure 2 ( A ) PXRD of a simulated pattern of ZnTPP NPs (a), ZnTPP NPs (b) 42 , ZnTPP/Ag NCs (c), ZnTPP/Ag/AgCl/Cu NCs (d), ZnTPP/Au/Ag/AgCl NCs (e), ( B ): UV–Vis spectra of H 2 TPP (a), ZnTPP (b), ZnTPP NPs (c) 42 , ZnTPP/Ag/AgCl NCs (d), ZnTPP/Ag NCs (e), ZnTPP/Au/Ag/AgCl NCs (f), ( C ): FT-IR spectra of H 2 TPP (a), ZnTPP (b), ZnTPP NPs (c) 42 , ZnTPP/Ag NCs (d), ZnTPP/Ag/AgCl/Cu NCs (e), ZnTPP/Au/Ag/AgCl NCs (f).
…”
Section: Resultsmentioning
confidence: 99%
“…In our previous research, the cytotoxic effect of porphyrin-based copper nanocomposites was confirmed on breast cancer cells . Herein, considering the biocompatibility, photoactivity, and applicable cancer therapy of a porphyrinic MOF [composed of a Zr 6 O 4 (OH) 4 cluster and a porphyrin ligand (H 2 TCPP)], in a green photochemical strategy, PCN-224/Au-NPs were produced.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 In our previous research, the cytotoxic effect of porphyrinbased copper nanocomposites was confirmed on breast cancer cells. 43 Herein, considering the biocompatibility, photoactivity, and applicable cancer therapy of a porphyrinic MOF [composed of a Zr 6 O 4 (OH) 4 cluster and a porphyrin ligand (H 2 TCPP)], in a green photochemical strategy, PCN-224/Au-NPs were produced. The investigation of the cytotoxic effect of the synthesized porpyrinic MOF-based nanocomposite was carried out utilizing the 3-(4,5-dimethylthiazol-2-yl)-2,5diphenyltetrazolium bromide (MTT) assay on colorectal cancer cells and human embryonic kidney (HEK)-293 normal cells as well.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, finding new photocatalyst materials has always been necessary to improve degradation. These materials have a variety of applications, 7 including reduction of CO 2 , degradation of organic contaminants, removal of toxic ions and heavy metal ions, water or air purification, self‐cleaning, and antibacterial properties 8,9 . ZnO has many features to become an environmentally friendly metal oxide and properties, such as inexpensive, safe, low toxicity, biodegradable, and easily prepared 10 .…”
Section: Introductionmentioning
confidence: 99%